HPV prevalence and type‐distribution in cervical cancer and premalignant lesions of the cervix: A population‐based study from Northern Ireland. Issue 7 (5th January 2016) - Anderson, Lesley A.; O'Rorke, Michael A.; Wilson, Robbie; Jamison, Jackie; Gavin, Anna T.; ,
Abstract : Assessment of Human papillomavirus (HPV) prevalence and genotype distribution is important for monitoring the impact of prophylactic HPV vaccination. This study aimed to demonstrate the HPV genotypes predominating in pre‐malignant and cervical cancers in Northern Ireland (NI) before the vaccination campaign has effect. Formalin fixed paraffin embedded tissue blocks from 2, 303 women aged 16–93 years throughout NI were collated between April 2011 and February 2013. HPV DNA was amplified by PCR and HPV genotyping undertaken using the Roche ® linear array detection kit. In total, 1, 241 out of 1, 830 eligible samples (68.0%) tested positive for HPV, with the majority of these [1, 181/1, 830 (64.5%)] having high‐risk (HR) HPV infection; 37.4% were positive for HPV‐16 (n = 684) and 5.1% for HPV‐18 (n = 93). HPV type‐specific prevalence was 48.1%, 65.9%, 81.3%, 92.2%, and 64.3% among cervical intraepithelial neoplasias (CIN) Grades I–III, squamous cell carcinomas (SCC) and adenocarcinoma (AC) cases, respectively. Most SCC cases (81.3%) had only one HPV genotype detected and almost a third (32.0%) of all cervical pathologies were HPV negative including 51.9% of CIN I (n = 283), 34.1% CIN II (n = 145), 18.7% of CIN III (n = 146), 7.8% of SCC (n = 5), and 35.7% of AC (n = 5) cases. This study provides important baseline data for monitoring the effect of HPV vaccination in NI and for comparison with other UK regions. The coverage of other HR‐HPV genotypes apart from 16 and 18, including HPV‐45, 31, 39, and 52, and the potential for cross protection, should be considered when considering future polyvalent vaccines. J. Med. Virol. 88:1262–1270, 2016 . © 2015 Wiley Periodicals, Inc.